Factors affecting financing of communal sanitation facilities by the public sector in Informal Settlements: A case of Nyalenda informal settlement, Kisumu City. (African Journal of Science, Technology and Social Sciences, 2024)
To close the current sanitation gap, public funding for sanitation has become increasingly insufficient, particularly in Sub-Saharan Africa. What is concerning in Kenya is not the large number of people who lack access to safe sanitation facilities, but the slow rate at which households can gain access to improved sanitation facilities. A sustainable financing strategy is required, one that will increase resource allocations to the sector, improve the efficiency and effectiveness of existing resources wherever they are found, and tap the potential of alternative financing mechanism. A critical review of policy documents like the County Integrated Development Plan (CIDP) shows that there is hardly any documentation on County sanitation plans. Once sanitation lacks in the CIDP, the county can hardly plan for the sector hence making the residents suffer. The study objectives are to examine different sanitation financing options for communal sanitation facilities in Nyalenda informal settlement, to assess factors affecting financing of communal sanitation facilities by public sector in Nyalenda informal settlement and to establish challenges of financing communal sanitation facilities in Nyalenda informal settlement. The study is a descriptive cross-section design. The study used closed and open-ended questionnaires and key informants’ interview in collection of data where n=400. The study established that the dominant communal sanitation financing option in Nyalenda informal settlement was personal contribution (56.0%), followed by NGO financing (40.3%), while the last was County Government financing (0.5%). Public-private partnerships played a crucial role in facilitating sustainable onsite financing for sanitation facilities as evidenced by majority of the respondents agreeing (35.75%). The study recommended the need for diverse financing sources, awareness of available options, and supportive policies to overcome financial challenges.
Keywords: Communal Financing; Sanitation; Slums; WASH